2016
DOI: 10.1039/c6sc02170k
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the coordination complex [Co(C3S5)2]2− from a molecular magnet to a potential qubit

Abstract: We employ ac susceptibility as a probe of small changes of transverse zero-field splitting, revealing that these subtle changes transform [Co(C3S5)2]2– from a molecular magnet to a candidate qubit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…On the other hand, at the higher θ d (or close to 90°) and lower 2 θ values (or close to 90°), the D becomes as negative as high as −120 cm −1 with a minimum E / D value. This trend also supports previously reported experimental results . In case of type I , the graph is smooth up to the higher polar angle of 108°, contrary to the entire correlation where there is a downward slope that has been observed at higher dihedral and polar angle ≈110°.…”
Section: Magneto‐structural Mapssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, at the higher θ d (or close to 90°) and lower 2 θ values (or close to 90°), the D becomes as negative as high as −120 cm −1 with a minimum E / D value. This trend also supports previously reported experimental results . In case of type I , the graph is smooth up to the higher polar angle of 108°, contrary to the entire correlation where there is a downward slope that has been observed at higher dihedral and polar angle ≈110°.…”
Section: Magneto‐structural Mapssupporting
confidence: 92%
“…It is to be noted here that we have not considered another important torsional angle parameter of X‐Co‐X‐Y ( ω ) as the ligands here are bidentate in nature and therefore ω does not vary much across the structures. It is observed that the axial and rhombic anisotropies ( D and E / D ) strongly depend on angle 2 θ and dihedral angle θ d …”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the deviation parameters of the octahedral Co 2+ center from ideal O h symmetry and of the tetrahedral Co 2+ center from ideal T d symmetry, continuous SHAPE measures of the Co 2+ ions were calculated to be 2.353 for Co1 in 1 and 2.708 and 0.199 for Co1 and Co2 in 2 , respectively. Notably, the CoN 4 tetrahedron of 2 deviates a little bit more from ideal T d symmetry than the very recently reported two compounds containing the [Co(NCS) 4 ] 2– anion,, which might influence the magnetic properties of the [Co(NCS) 4 ] 2– anion . For the cationic part, the shortest Co1 ··· Co1 distances are 13.4 and 8.9 Å for 1 and 2 , respectively.…”
Section: Resultsmentioning
confidence: 80%
“…1,3,6 Among the features of interest are the inner coordination sphere, e.g. geometry,1418 vibrations,1921 nuclear-spin content,14,15,2228 and electronic spin magnitude 15,24,25. Such investigations have provided impressive results, potentially enabling molecular information storage near and above liquid N 2 temperatures 2931.…”
Section: Introductionmentioning
confidence: 99%